Influence Of Church Governance On The Level Of Congregational Giving: A Case Of Christian Churches In Utawala Ward, Nairobi, Kenya. - Musau, Nicholas Muasa; Kibuthu, Isaac Muitherero; Nyaga, Rahab N. (International Journal of Scientific and Research Publications, 2020)
The issue of giving in the church has been approached with a lot of skepticism. Most churches experience difficulties in the way they have to teach their congregants on the importance of giving. More often than not, it is wondered why some people give while others do not, yet they go through the same kind of spiritual teachings. This study was undertaken with a purpose of examining the influence of church governance on the level of giving. The independent construct was church governance. The indicators of governance were consistency, accountability, integrity and transparency. The level of giving on the other hand was the dependent construct. The research was a descriptive survey study with quantitative method of data collection that was conducted in Utawala ward in Nairobi, Kenya. Purposive sampling was used to select five churches from a population of over thirty churches, and stratified sampling to select different clusters within the same church. Data was collected using a self-administered questionnaire and oral interviews to selected leaders within the same churches. The study found that transparency, integrity, accountability and consistency influenced the level of giving in the church. Indeed, the study indicated that integrity played a key role in congregational giving and determined how much was given especially on projects. In the churches that practiced accountability and transparency, the level of giving was high while in those that did not, the level of giving was low. Further, in the churches that were consistent and especially in matters of exercising their constitution, the level of giving was high. The study concluded that in the leadership of those churches that presented financial reports, this was done consistently, there were structures in place to ensure accountability and there was a constitution in place to ensure consistency. The study recommends that leaders of churches should endeavor to be fair to all the faithful as fairness is a matter of perception and that the church diversifies its sources of funding by engaging in income generating activities for example church based schools which could improve their financial situation.